2021
DOI: 10.12688/f1000research.52606.2
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Spontaneous simultaneous coronary and carotid dissection in a young cannabis user

Abstract: Due to legalization of its consumption in some countries and its medical use as well as low toxic potential, cannabis remains the most widely used drug around the world and the rate of usage is only increasing.  Nevertheless, there are several case reports of vascular complications following cannabis use even in young people without cardiovascular risk factors. We report the case of a cannabis smoker presenting to the emergency room for an ischemic stroke associated with an acute coronary syndrome related to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…There were 23 studies identified that included patients presenting with cannabis induced ischemic stroke [ Table 4 ]. [ 3 , 6 , 11 , 16 , 17 , 19 , 21 , 27 , 29 , 39 , 44 , 50 , 57 - 59 , 61 , 63 , 64 , 67 - 69 , 71 , 72 ] Demographic information was available in 22 articles for a total of 44 patients (10/44 [23%] female) with a median age of 28 years. All included studies described clinical presentation for the 184 total patients, which consisted of headache (2%), speech disturbance (64%), abnormal sensation/ motor function (38%), and visual disturbance (14%).…”
Section: Resultsmentioning
confidence: 99%
“…There were 23 studies identified that included patients presenting with cannabis induced ischemic stroke [ Table 4 ]. [ 3 , 6 , 11 , 16 , 17 , 19 , 21 , 27 , 29 , 39 , 44 , 50 , 57 - 59 , 61 , 63 , 64 , 67 - 69 , 71 , 72 ] Demographic information was available in 22 articles for a total of 44 patients (10/44 [23%] female) with a median age of 28 years. All included studies described clinical presentation for the 184 total patients, which consisted of headache (2%), speech disturbance (64%), abnormal sensation/ motor function (38%), and visual disturbance (14%).…”
Section: Resultsmentioning
confidence: 99%